Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1063/1.4968301
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polymer concentration on flux stability of polysulfone membrane

Abstract: Abstract. The influence of various polymer concentrations on flux stability of polysulfone membranes was investigated. The polysulfone membrane was prepared by blending polysulfone in DMAc with 25%wt concentration of PEG400 and 4% wt concentration of acetone. It was found that the pure water flux was sharply decreased from 1230 to 7 Lm-2h-1, when the polysulfone concentration was increased from 14% to 24%wt. Furthermore, the increase of polysulfone concentration also affects the fouling behavior of the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Flux values decreased significantly due to the increasing concentration of M. oleifera seeds powder to the mixed materials. The same result was obtained in a different study [41], with their work on of high flux polysulfone membranes. Another research was done and reported that high flux membranes were produced, and testing the performance in a constant flux test [42].…”
Section: Effect Of Adding M Oleifera Seeds Powder On Membrane Fluxsupporting
confidence: 85%
“…Flux values decreased significantly due to the increasing concentration of M. oleifera seeds powder to the mixed materials. The same result was obtained in a different study [41], with their work on of high flux polysulfone membranes. Another research was done and reported that high flux membranes were produced, and testing the performance in a constant flux test [42].…”
Section: Effect Of Adding M Oleifera Seeds Powder On Membrane Fluxsupporting
confidence: 85%
“…The selectivity of the membrane is improved by the addition of acetone into the polymer solution, which resulted in higher rejection of humic acid [29]. In other research, The effect of PSf concentration on the UF membrane performances during peat water filtration at various operating pressure [30]. They blended PSf polymer with PEG400 (25%wt) and acetone (4%wt) in DMAC solvent.…”
Section: ''""mentioning
confidence: 99%
“…The experimental procedures refer to our previous work, as shown in Figure 2 [29,30]. A circular UF membrane module was used to measure water flux and rejection of humic acid during 2 (two) hours of peat water filtration.…”
Section: Flux and Selectivity Measurementmentioning
confidence: 99%
“…The separation performances of a polymer membrane are determined by its intrinsic properties such as polymer crystallinity, hydrophobicity/hydrophilicity, generated charge, surface roughness, as well as porous structure across the membrane [13][14][15][16]. According to their average pore diameter, membranes can be classified into four classes: (1) conventional filtration (10-100 µm), microfiltration (0.1-10 µm), ultrafiltration (1-100 nm) and reverse osmosis (~0.1 nm) [17,18].…”
Section: Introductionmentioning
confidence: 99%